Tantangan dan Strategi Konselor Pemula dalam Praktik Bimbingan dan Konseling di Era Digital - Gusman Lesmana; Nur Ajizah Panjaitan; Rika Ayuni; Mega Natasya; Nurhaliza Nurhaliza; Wida Melani; Dian Hikmah Br Tarigan (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to identify challenges faced by novice counselors in guidance and counseling practice in the digital era and strategies that can be applied to overcome them. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews with 12 novice counselors who have practiced for 1-3 years in secondary schools and universities. The results show that novice counselors face main challenges including: (1) limited technological competence in online counseling services, (2) difficulty building rapport in virtual sessions, (3) security and confidentiality issues of client data, (4) adaptation to changes in counselee behavior influenced by digital technology, and (5) lack of supervision and mentoring in digital counseling context. Effective strategies include improving digital literacy through continuous training, using secure counseling platforms, developing virtual communication skills, collaborating with senior counselors, and utilizing technology as intervention support tools. This research provides practical implications for the development of novice counselor competencies and recommendations for educational institutions in preparing prospective counselors for the digital era.